85. Treatment of hepatocarcinoma with 90Y glass microspheres: Safety and indication of prolonged overall survival thanks to two compartment dosimetric treatment planning. (December 2018) - Chiesa, C.; Mira, M.; Maccauro, M.; Spreafico, C.; Cascella, T.; Sposito, C.; Bhoori, S.; De Nile, M.C.; Seregni, E.; Marchianò, A.; Crippa, F.; Mazzaferro, V.
Abstract : Purpose: To check the impact on toxicity and on overall survival (OS) of a personalized two compartment (tumor vs non tumor) dosimetric treatment planning method in the treatment of hepatocarcinoma with 90 Y glass microspheres. Methods: 43 Child A strictly selected patients (series 1) had been previously treated with 90 Y glass microspheres according to the standard mono-compartment planning of 120 Gy to the injected liver lobe. A retrospective analysis of 99m Tc-MAA pre-treatment SPECT/CT images had allowed to determine NTCP and TCP[1] . A decompensation risk of 15% was adopted as planning limit, corresponding to NTCP15 = 75 Gy. Liver absorbed dose is averaged on the organ volume excluding tumors. Such planning method was then applied to 116 less selected Child A patients (series 3, comparable to series 1). Results: With respect to series 1, administered activity in series 3 was doubled in half of patients, reduced of 50% in a quarter of patients. Toxicity rate was maintained below 15%. Patient were stratified as advanced (with Portal Vein Thrombosis (PVT)) vs intermediate (NO PVT). In the PVT subgroups, lesions had the same size distribution. Treatment planning improved median OS from 8 to 12 months (with Mantel Cox test (p = 0.067) i.e. close to significance). In the NO PVT subgroups the median OS was 17 vs 15 months (n.s.) i.e. maintained, despite the larger tumor sizes. Conclusions: methodological limits were absence of scatter correction and mismatch between simulation and 90 Y PET dosimetry. Results are really encouraging, since are the first indications of improved outcome thanks to dosimetric treatment planning.